2021
DOI: 10.1038/s41467-021-23125-9
|View full text |Cite
|
Sign up to set email alerts
|

Human stem cells harboring a suicide gene improve the safety and standardisation of neural transplants in Parkinsonian rats

Abstract: Despite advancements in human pluripotent stem cells (hPSCs) differentiation protocols to generate appropriate neuronal progenitors suitable for transplantation in Parkinson’s disease, resultant grafts contain low proportions of dopamine neurons. Added to this is the tumorigenic risk associated with the potential presence of incompletely patterned, proliferative cells within grafts. Here, we utilised a hPSC line carrying a FailSafeTM suicide gene (thymidine kinase linked to cyclinD1) to selectively ablate prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 39 publications
2
37
1
Order By: Relevance
“…Recent studies have highlighted the importance of SDF1 in DA development [20][21][22], and the DA differentiation of pluripotent stem cells [16][17][18][19]. Added to this, we previously demonstrated that the co-transplantation of meningeal cells, together with VM fetal grafts, significantly increased the proportion of A9 DA neurons within VM grafts-an effect that was speculated to be modulated via SDF1-CXCR4 signalling [22].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Recent studies have highlighted the importance of SDF1 in DA development [20][21][22], and the DA differentiation of pluripotent stem cells [16][17][18][19]. Added to this, we previously demonstrated that the co-transplantation of meningeal cells, together with VM fetal grafts, significantly increased the proportion of A9 DA neurons within VM grafts-an effect that was speculated to be modulated via SDF1-CXCR4 signalling [22].…”
Section: Discussionmentioning
confidence: 77%
“…More recently, a series of studies have provided new insight into the role of the chemokine Stromal cell-Derived Factor-1, SDF1 (also known as CXCL12), and the meninges in midbrain DA development to suggest that this protein may also improve graft outcomes. Several studies demonstrated that the co-culture of embryonic stem cells on stromal cell feeder layers, or meningeal cells, promoted neural induction and induced DA differentiation via secreted factors termed stromal derived inducing activity (SDIA) [16][17][18][19]. Genome expression analysis revealed that SDF1 was one of the secreted factors [19].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, long-term safety of hiPSC therapies requires the elimination of their tumorigenic potential by ensuring use of non-integrating reprogramming factors, uniform and robust differentiation protocols, and identification and removal of pluripotent or immature, proliferating cells (99). Specifically, generation of hiPSC lines with drug-inducible suicide genes can be utilized to partially or fully eradicate transplanted cells in cases of adverse outcomes in vivo (100).…”
Section: Hipsc-based Therapymentioning
confidence: 99%
“… 6 , 7 However, iPSC-derived muscle cells do not yet meet quality and safety criteria for transplantation into patients. Overall, allogeneic transplantation requires immunosuppression or cloaking of transplantable cells, 8 , 9 adding another level of uncertainty, and it has not yet been shown for iPSC-derived muscle cells. In addition, MuSCs are irreplaceable in muscle regeneration; 10 , 11 thus, a long-term therapeutic effect of a stem cell therapy would require that the transplanted cells can reconstitute the MuSC compartment.…”
Section: Introductionmentioning
confidence: 99%